Antiproteinuric and Hyperkalemic Mechanisms Activated by Dual Versus Single Blockade of the RAS in Renovascular Hypertensive Rats - Corrêa, José Wilson N.; Boaro, Karoline R.; Sene, Letícia B.; Polidoro, Juliano Z.; Salles, Thiago A.; Martins, Flavia L.; Bendhack, Lusiane M.; Girardi, Adriana C. C. (Frontiers in Physiology, 2021)
This study aimed to investigate the antiproteinuric and hyperkalemic mechanisms activated by dual renin-angiotensin system (RAS) blockade in renovascular hypertensive rats (2-kidney 1-clip model (2K-1C)). Six weeks after clipping the left renal artery or sham operation (2K), rats were treated with losartan, enalapril, or both drugs, for two weeks. 2K-1C rats displayed higher tail-cuff blood pressure (BP), increased non-clipped kidney Ang II concentration, and more pronounced urinary albumin excretion than 2K. BP was decreased by the treatment with either enalapril or losartan, and the combination of both drugs promoted an additional antihypertensive effect in 2K-1C rats. Renal Ang II content and albuminuria were reduced by either enalapril or losartan in monotherapy and restored to control levels by dual RAS blockade. Albuminuria in 2K-1C rats was accompanied by downregulation of the glomerular slit protein podocin, reduction of the endocytic receptors, megalin, and cubilin, and a marked decrease in the expression of the ClC-5 chloride channel, compared to 2K animals. Treatment with losartan and enalapril in monotherapy or combination increased the expression of podocin, cubilin, and ClC-5. However, only the combined therapy normalized podocin, cubilin, and ClC-5 protein abundance in the non-clipped kidney of 2K-1C rats. Renovascular hypertensive 2K-1C rats had a lower concentration of plasma potassium compared to 2K rats. Single RAS blockade normalized potassium plasma concentration, whereas 2K-1C rats treated with dual RAS blockade exhibited hyperkalemia. Hypokalemia in 2K-1C rats was accompanied by an increase in the cleaved activated forms of α-ENaC and γ-ENaC and the expression of β-ENaC. Combined RAS blockade but not monotherapy significantly reduced the expression of these ENaC subunits in 2K-1C rats. Indeed, double RAS blockade reduced the abundance of cleaved-α-ENaC to levels lower than those of 2K rats. Collectively, these results demonstrate that the antiproteinuric effect of dual RAS blockade in 2K-1C rats is associated with the restored abundance of podocin and cubilin, and ClC-5. Moreover, double RAS blockade-induced hyperkalemia may be due, at least partially, due to an exaggerated downregulation of cleaved α-ENaC in the non-clipped kidney of renovascular hypertensive rats.